1994
DOI: 10.1038/sj.npp.1380162
|View full text |Cite
|
Sign up to set email alerts
|

Diet and Gender Moderate Clozapine-Related Weight Gain

Abstract: This study examined patients with schizophrenic disorders treated with clozapine in a state hospital setting. Gender and diet affected weight gain over a six-month period. Pre-treatment weight status also related to eventual weight gain. There were no significant effects of dosage. Weight gain was most pronounced in non-dieting women. This has implications for management of patients on clozapine

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0
1

Year Published

2000
2000
2006
2006

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(19 citation statements)
references
References 9 publications
0
18
0
1
Order By: Relevance
“…Factors affecting management of weight gain are negative symptoms, cognitive impairment, low income level, preference of highcalorie food, impaired satiety, level of sedation and reduced ability to handle daily hassles (e.g., shopping and cooking) (Sharpe and Hills 2003). In hospitalised, clozapine-treated patients with preexisting physical or metabolic defects, dietary restriction led to mean weight loss of 7.1 kg in men and 0.5 kg in women compared to weight gain of 2.0 kg in men and 6.1 kg in women not dieting over 6 months (Heimberg et al 1995). In a residential setting, a low-fat, low-calorie diet was not able to change average body weight over 2 years, but clozapine-and olanzapine-treated patients who gained weight were able to lose it during this nutrition counselling programme (Aquila and Emanuel 2000).…”
Section: Obesity and Weight Gainmentioning
confidence: 99%
“…Factors affecting management of weight gain are negative symptoms, cognitive impairment, low income level, preference of highcalorie food, impaired satiety, level of sedation and reduced ability to handle daily hassles (e.g., shopping and cooking) (Sharpe and Hills 2003). In hospitalised, clozapine-treated patients with preexisting physical or metabolic defects, dietary restriction led to mean weight loss of 7.1 kg in men and 0.5 kg in women compared to weight gain of 2.0 kg in men and 6.1 kg in women not dieting over 6 months (Heimberg et al 1995). In a residential setting, a low-fat, low-calorie diet was not able to change average body weight over 2 years, but clozapine-and olanzapine-treated patients who gained weight were able to lose it during this nutrition counselling programme (Aquila and Emanuel 2000).…”
Section: Obesity and Weight Gainmentioning
confidence: 99%
“…Only 9 studies reported drop-out rates (21,(25)(26)(27)(28)(29)(30)(31)(32) with mean attrition rate of 47.52%, and a range from 9.7% -90%. Ten studies were conducted with inpatient populations (22,23,26,(33)(34)(35)(36)(37)(38)(39), 4 studies were conducted in residential treatment settings (25,40), partial hospitalization (31) or day treatment centers (32), and 9 were conducted with outpatient populations (21,24,(27)(28)(29)(30)(41)(42)(43). Two reports were chart reviews (30,41), 4 were case studies (33,35,37,38), 7 studies utilized a pre-post design (22)(23)(24)(25)(26)28,43), 6 were quasi experimental, using a crossover (34) or case control design (21,…”
Section: Overviewmentioning
confidence: 99%
“…Ten studies were conducted with inpatient populations (22,23,26,(33)(34)(35)(36)(37)(38)(39), 4 studies were conducted in residential treatment settings (25,40), partial hospitalization (31) or day treatment centers (32), and 9 were conducted with outpatient populations (21,24,(27)(28)(29)(30)(41)(42)(43). Two reports were chart reviews (30,41), 4 were case studies (33,35,37,38), 7 studies utilized a pre-post design (22)(23)(24)(25)(26)28,43), 6 were quasi experimental, using a crossover (34) or case control design (21,27,31,32,39), and 4 studies utilized a randomized controlled design (29,36,40,42). Mean duration of treatment was 25.68 weeks, excluding two studies which examined short educational interventions …”
Section: Overviewmentioning
confidence: 99%
“…São fatores que afetam o gerenciamento do ganho de peso: presença de sintomas negativos, comprometimento cognitivo, baixo nível econômico, preferências por alimentos calóricos, saciedade prejudicada, nível de sedação e reduzida habilidade para lidar com problemas diários (como fazer compras e cozinhar) (Sharpe e Hills, 2003). Entre os pacientes hospitalizados com doenças metabólicas ou físicas preexistentes tratados com clozapina, a restrição alimentar proporcionou uma perda média de 7,1 kg entre os homens e de 0,5 kg entre as mulheres, contra um ganho de peso de 2 kg entre os homens e de 6,1 kg entre as mulheres que não fizeram dieta no período de 6 meses (Heimberg et al, 1995). Em ambiente residencial, uma dieta hipocalórica e com baixo percentual de gordura não se mostra capaz de alterar a média de peso corporal por 2 anos, mas os pacientes tratados com clozapina e olanzapina que ganharam peso emagreceram durante esse programa de aconselhamento nutricional (Aquilla e Emanuel, 2000).…”
Section: Obesidade E Ganho De Pesounclassified